2020
DOI: 10.3389/fmed.2020.581763
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for COPD at High Altitude: A Large Cross-Sectional Survey of Subjects Living Between 2,100–4,700 m Above Sea Level

Abstract: Aim of Study: Four hundred million people live at high altitude worldwide. Prevalence and risk factors for COPD in these populations are poorly documented. We examined the prevalence and risk factors for COPD in residents living at an altitude of 2,100–4,700 m.Methods: We performed a cross-sectional survey in Xinjiang and Tibet autonomous region. A multistage stratified sampling procedure was used to select a representative population aged 15 years or older from eight high altitude regions. All participants un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 44 publications
4
30
0
Order By: Relevance
“…In our study, although the majority of the patients had mild-to-moderate COPD, breathlessness was the predominant symptom and the proportion of patients with a CAT score ≥10 was very high (~90%), indicating that respiratory symptoms were heavy in these individuals. A large population-based study showed that more than one half of COPD individuals living at high altitude had at least one respiratory symptom and 87.2% had a CAT score ≥10, 9 which was consistent with our study. Dyspnea was the most frequent symptom in this study, but the frequency was not as high as in our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, although the majority of the patients had mild-to-moderate COPD, breathlessness was the predominant symptom and the proportion of patients with a CAT score ≥10 was very high (~90%), indicating that respiratory symptoms were heavy in these individuals. A large population-based study showed that more than one half of COPD individuals living at high altitude had at least one respiratory symptom and 87.2% had a CAT score ≥10, 9 which was consistent with our study. Dyspnea was the most frequent symptom in this study, but the frequency was not as high as in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Dyspnea was the most frequent symptom in this study, but the frequency was not as high as in our study. 9 This may be due to different study designs. Asymptomatic mild COPD patients were less likely to visit the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, altitude itself had no significant impact on COPD prevalence [ 291 , 292 ]. Importantly, subjects with airflow limitation living at high altitude reported significantly fewer respiratory symptoms compared to subjects residing at lower altitude, and high altitude residence was associated with a significantly increased risk of undiagnosed COPD [ 292 , 293 ].…”
Section: Other Clinical Forms Of Pulmonary Hypertension At High Almentioning
confidence: 99%
“…Thus, other common causes of secondary pulmonary hypertension in lowlanders may underlie and/or contribute to pulmonary hypertension in high altitude residents. The challenges of detection of the underlying causes of pulmonary hypertension in high altitude residents are related to the asymptomatic course of the disease, low educational level of highlanders, limited access to facilities for diagnosis, and high rates of unawareness and low index of suspicion by local physicians [ 293 ].…”
Section: Other Clinical Forms Of Pulmonary Hypertension At High Almentioning
confidence: 99%